Reuters Institute digital news report 2019 - Newman, N; Fletcher, R; Kalogeropoulos, A; Nielsen, R (Reuters Institute for the Study of Journalism, 2019)
This year's report reveals new insights about digital news consumption based on a YouGov survey of over 75,000 online news consumers in 38 countries including South Africa for the first time. The report focuses on the progress on new paid online business models, trust and misinformation, the impact of populism, the shift to private messaging apps, and the rise of podcasts.